Creating metal saturated growth in MOCVD for CdTe solar cells - Stuart Irvine (Journal of Crystal Growth, 2023)
Determining the thermodynamic conditions in MOCVD growth of II-VI semiconductor materials is not as straightforward as in III-V growth where Group V hydrides are generally used. This paper establishes a technique, using in situ laser reflectometry, to ensure that the thermodynamic equilibrium is under metal saturated growth. This has been applied to the arsenic doping of CdTe solar cells where it was shown that increasing the II/VI precursor ratio resulted in an increase in As dopant incorporation. The growth kinetics were determined by the diisopropyl tellurium (DIPTe) concentration for II/VI precursor ratios above 2. A method is presented where the change in II/VI precursor ratio can be predicted for different positions in a horizontal MOCVD chamber that has, in turn, enabled variation in NA and the solar cell open circuit voltage (Voc) to be determined as a function of the II/VI precursor ratio. This gives new insight to the thermodynamic drivers in MOCVD growth for improved solar cell Voc and is a method that could be applied to MOCVD of other II-VI semiconductors.